39 spatial arrangement of the animal male germ cell genome: II. 2d-3d Simulation and visualization of spatial configuration of major chromosome 2 in Drosophila sperm - Alexandrov, Igor D.; Stepanenko, Victor A.; Alexandrova, Margarita V. (İstanbul Kültür Üniversitesi, 2007)
Data on the non-random distribution of radiationinduced inversion breakpoints were used as genetic markers for 2D and 3D modeling of the largescale architecture of the chromosome 2 in Drosophila sperm genome at the time of irradiation. During modeling, Gmax program with application of splines, the additional objects and operations as well as the methods of visualization of macromolecular biostructures were employed. A specific megarosette-loop model of spatial arrangement of chromatin fiber in the haploid sperm nucleus can account well for the experimental data.
Keywords: 2D/3D models; large-scale chromosome geometry; sperm genome; Drosophila; 2D/3D modelleri; sperm genom; büyük ölçekli kromozom geometrisi